AUTHENTIC MATERIALS TO DEVELOP READING COMPREHENSION SKILLS AMONG INTERMEDIATE AND ADVANCED ESL LEARNERS (SCIENCE TIME JOURNAL, 2026)
Authentic materials have a significant place in contemporary English language teaching, as they provide learners with exposure to real-world language an purposeful communication. This article examines how authentic materials contribute to thedevelopment of reading comprehension skills among intermediate and advanced ESL learners. Materials such as newspapers, magazines, online articles, advertisements, blogs, and academic texts support students in expanding their vocabulary, improving reading fluency, strengthening critical thinking, and increasing cultural awareness. In contrast to simplified texts found in textbooks, authentic reading materials present natural language structures and real-life contexts, helping learners become better prepared for both academic and everyday communication.